Model Tarikan Perjalanan Pengunjung Pusat Perbelanjaan Java Mall Semarang - Ovi Septi Anggraeni; Yudi Basuki (Jurusan Perencanaan Wilayah dan Kota, 2022)
Java Mall is a shopping center in the city of Semarang which is located on a secondary collector road, namely the MT. Haryono which is the main trade route of the city of Semarang and is included in one of the Petawangi areas (Peterongan - Tawang - Siliwangi), namely the Peterongan trading area. The development of the development of the Java mall is a special attraction for visitors because every month there are events in the form of computer exhibitions, property, cars, etc., in addition there are cinemas and food markets. The problem that occurred in this research location is the traffic jams that occur due to the influence of the pull of the Java Mall shopping center directly accessed on Jl. MT. Haryono (Semarang). Congestion occurs on the road in front of the Java Mall due to the pull of the Java Mall so that new activities arise such as the use of road bodies for parking vehicles, online motorcycle taxi stops on the shoulder of the road, and street vendors who use the shoulder of the road. Based on these problems, preliminary research was conducted on travel attraction modeling to understand the contribution of Java Mall visitor vehicles to Mt. Haryono based on the development of the area of Java Mall activities. In this study quantitative methods are used. Trip attraction modeling in multi-activity shopping centers is influenced by the floor area of each building shown by the equation Y = 0.003 + 0.151 X1 + 0.052 X2 + 0.066 X3 + 0.091 X4. Calculation of the total trip rate of visitors resulting in a trip attraction generated by the Java Mall during peak hours is 0.066 people / m2, in this case the development of the Java Mall building is considered quite effective with several areas of activity therein.